Kategoryzacja obiektów noclegowych zlokalizowanych na obszarach wiejskich w polskiej części euroregionu Nysa - Jaremen, Daria E.; Nawrocka, Elżbieta (Grading of Accommodation Facilities Situated in Rural Areas in the Polish Part of Nysa Euroregion, 2005)
The increase of market competitiveness as well as changes in consumers' behaviour result in favourable timing for upgrading of services' quality and better adjustment of their parameters to expectations and requirements of consumers, with reference to Polish rural tourism. The article takes up an attempt of presenting the importance of accommodation facilities grading in the process of rural tourism standards' upgrading, as well as the assessment of grading standards common application by the accommodation facilities situated in the Polish part of the Nysa Euroregion. For this reason determinants responsible for shaping the quality of accommodation services are identified and divided into those dependent and independent from the services' provider. There has also been discussed the essence and the role of grading itself. The process of hotel facilities' grading in Poland has been presented with particular emphasis on the system referring to rural accommodation facilities. Final remarks cover the issue of accommodation facilities' grading system implementation advancement in the researched area and the reasons underlying the identified state of the matter.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 130-140